Implementation of the Agriculture-Based Welfare Poverty Surgery Program in Community Empowerment - Umar Congge; Abd. Wahid; Irmawati Irmawati; Mirnawati. E (Jurnal Office, 2021)
Community empowerment is a way of social, economic, and political change to empower and strengthen community capacities through participatory learning. This study aims to find out how the Implementation of the Agricultural-Based Surgery for Poverty Program (BEKERJA acronym in Indonesian) in Community Empowerment in Kalero Village, this study uses a qualitative descriptive type which is intended to provide a clear picture and overall description of the existing problems. This research was conducted in Kalero Village, Kajuara District, Bone Regency. Data collection is done through the methods of observation, interviews, and documentation. Data obtained were analyzed based on the indicators determined by looking at the results of observations, interviews, and documentation from research informants. Informants used was the Head of the Kajuara Sub-district, the Head of Kalero Village, the Community who received the BEKERJA Program Assistance, Village Level Facilitators, and District Level Facilitators. Results of this study stated that the Implementation of the Agriculture-Based Welfare Poverty Surgery Program (BEKERJA) in Community Empowerment in Kalero Village did not run optimally, this was due to many factors, the first of which was feed factors that were not on target or wrong feed and weather factors that caused failure or failure not successful.